Georgina Beier, Mathias Kauage, seine Frau und sein Sohn im Iwalewahaus (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Photographs; Artists; Papua New Guinea; New Guinea; Iwalewahaus; Cultural Centre; Performing Arts Center